Impact of an adapted diabetes prevention program in a spanish primary care setting: protocol for a type II hybrid effectiveness-implementation cluster-randomized trial (ALADIM) - Miquel Bennasar-Veny; Manuela Abbate; Miquel Colom-Rosselló; Laura Capitán-Moyano; Ivonne C. Hernández-Bermúdez; Ignacio Ricci-Cabello; Aina M. Yañez; Maria E. Fernandez; the ALADIM investigators (Implementation Science)
Abstract Background Type 2 diabetes (T2D) is a global health concern affecting 10.5% of the adult population and is projected to rise significantly in the coming decades. Lifestyle modification programs, such as the Diabetes Prevention Program (DPP), can effectively reduce T2D risk among individuals with prediabetes. However, their implementation in real-world healthcare settings remains poor, particularly in Spain, where T2D prevalence is the highest in Europe. The ALADIM study aims to evaluate the effectiveness and implementation of an adapted DPP in Spanish Primary Care Centers (PCCs). The primary effectiveness outcome is weight, the co-primary implementation outcome is implementation fidelity. We will also assess the effect of DPP implementation on overall prediabetes management within the PCCs (spillover) by measuring the percentage of people with prediabetes receiving lifestyle advice. Methods The ALADIM trial is a hybrid type II effectiveness-implementation cluster-randomized controlled trial involving 10 PCCs of Mallorca (Balearic Islands, Spain). PCCs will be randomized to the intervention (5 PCCs) or control (5 PCCs) group in a 1:1 ratio. The intervention group will receive training and materials to implement and deliver the adapted DPP over 12 months. The control group will continue providing usual care. The DPP will be culturally adapted using the Intervention Mapping-ADAPT (IM-ADAPT) approach. The implementation strategy will be designed using Implementation Mapping. Measures of effectiveness will be assessed at the participant level at baseline, 6 and 12 months during the intervention period, and 18 months after baseline. Implementation outcomes will be assessed at the PCC level at multiple time-points throughout the study period. Spillover will be assessed at PCC level at months -1, 6 and 18. An intention-to-treat analysis will assess effectiveness and spillover effect using generalized estimating equations. Implementation outcomes will be evaluated using a mixed-methods approach. Discussion The ALADIM study has the potential to address the gap between research and practice by employing implementation science for evaluation, adaptation and implementation of an evidence-based diabetes intervention. The findings will contribute to the development of a sustainable and scalable implementation strategy for T2D prevention, with potential implications for policy and practice at regional and national levels. Trial registration ClinicalTrials.gov, NCT06871059. Registered 10 March 2025, https://clinicaltrials.gov/study/NCT06871059